Pengembangan Bahan Ajar Berbasis Metode ABA dalam Pembelajaran Matematika untuk Meningkatkan Kemandirian Siswa - Rahmania, Rahmania; Maritasari, Donna Boedi; Marsa Ibrahim, Doni Septu; Sururuddin, Sururuddin (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This research is motivated by the low independence of elementary school students in mathematics, especially fractions, due to conventional methods and the lack of innovative teaching materials. The objective is to develop and test the effectiveness of Applied Behavior Analysis (ABA)-based mathematics teaching materials to improve student independence. Using the ADDIE development model, this research began with an analysis of student needs and the curriculum. The design stage included designing a fraction addition module, including visual elements. Development involved validation by material and media experts, as well as revisions. Implementation was carried out through a trial in grade V of SD Negeri 1 Moyot, with data from response questionnaires and learning outcome tests. Product evaluation showed that this teaching material was very feasible (media experts 98%, material experts 80%). Student responses were positive ("Good" 66.48%), and learning outcomes improved ("Good" 75.64%), with classical completeness of 76%. The implication is that ABA teaching materials are effective in improving student independence and mathematics learning outcomes, and serve as a reference for the development of innovative teaching materials